Robot Control Using Alternative Trajectories Based on Inverse Errors in the Workspace. (16th August 2021) - Duong, Quoc Khanh; Trang, Thanh Trung; Pham, Thanh Long
Abstract : It is easy to realize that most robots do not move to the desired endpoint (Tool Center Point (TCP)) using high-resolution noncontact instrumentation because of manufacturing and assembly errors, transmission system errors, and mechanical wear. This paper presents a robot calibration solution by changing the endpoint trajectories while maintaining the robot's control system and device usages. Two independent systems to measure the endpoint positions, the robot encoder and a noncontact measuring system with a high-resolution camera, are used to determine the endpoint errors. A new trajectory based on the measured errors will be built to replace the original trajectory. The results show that the proposed method can significantly reduce errors; moreover, this is a low-cost solution and easy to apply in practice and calibration can be done cyclically. The only requirement for this method is a noncontact measuring device with high-resolution and located independently with the robot in calibration.